Multi-Response Optimization of Bambara Nut Milling-Sieving Machine - Francisca, Ikechukwu Ijeoma (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Response Surface Experimental design was used to investigate the optimal operational parameters and response of Bambara nut milling–sieving machine; Performance result revealed particle size of milled flour, number and speed of the paddle as these machine process/operational parameters with significant influence on its performance while throughput and extraction efficiency constitutes its functional performance indicators. Extraction of the grain starch granules from its fiber depends on the particle size of the milled grain and paddle parameters. In addition, the multi-response performance simulation of this machine predict 1080 rpm, 4 paddles and 35 μm respectively for speed of the paddles, number of paddles and particle size of bambara flour as values require for its optimal operation with optimal value of throughput and extraction efficiency of 117.8 kg/h and 98.45% respectively which indicates that the novel bambara nut milling-sieving machine reduced the food loss to chaff in this sector to 1.55% against 15.82% associated with the widely used semi-mechanized system. It also promotes hygiene in this sector because it eliminated human contact with the milled grain during sieving operation. Its operation with the optimal parameters derived in this study is therefore recommended to both small and medium scale bambara flour producers to enhance quantity and quality bambara flour production for food security and poverty alleviation.